Delivery balloon rupture during transcatheter heart valve alignment procedure in extreme descending aorta tortuosity - Sumimoto, Yoji (J Cardiol Cases, 2019)
A 79-year-old man with a history of partial resection of the lung and the bladder due to cancer, hypertension, dyslipidemia, and heart failure, underwent transcatheter aortic valve replacement with a SAPIEN 3 (S3) valve (Edwards Lifesciences, Irvine, CA, USA). Preprocedural examination showed a bicuspid aortic valve and severe calcification of the leaflets. Computed tomography showed great tortuosity of the descending aorta. A 29-mm S3 valve prosthesis was advanced into the aorta, but a high degree of resistance was encountered in the middle of the descending aorta. The prosthesis was advanced to the level of aortic valve and an attempt was made to deploy the valve. However, the valve balloon did not expand. A balloon rupture was suspected. The balloon catheter was pulled back into the eSheath (Edwards Lifesciences), and the catheter and eSheath were removed together. Rupture of the balloon was confirmed. A new eSheath and prosthesis were prepared, with delivery supported with a Lunderquist guidewire (Cook Medical, Bloomington, IN, USA). The valve alignment procedure was performed in a straighter portion of the descending aorta. The new 29-mm S3 valve was then successfully implanted. <Learning objective: Rupture of the balloon during transcatheter aortic valve replacement is a rare, potentially fatal complication. A case of balloon rupture during a valve alignment procedure with successful retrieval is reported along with a review of the complication involved.>